A new species of Guadua (Poaceae: Bambusoideae: Guaduinae) from Pará state in Amazonian Brazil - Lobato Afonso, Edgar Augusto; Clark, Lynn G.; Mansano, Vidal De Freitas; Filgueira, Joana Patrícia Pantoja Serrão; Viana, Pedro Lage (Phytotaxa, 2023)
A new species of Guadua, a Neotropical woody bamboo genus, is here described and illustrated. Guadua leonardoana occurs in southeastern Amazonia, northern Brazil, in rainforest vegetation, and apparently is endemic to Pará state, with only two known populations restricted to the Serra dos Carajás. This species belongs to the “Guadua weberbaueri group” and the description is based on vegetative features. A morphological description, illustrations, photos in the field, scanning electronic micrographs of the foliage leaf surfaces, data on anatomy and micromorphology of the foliage leaf blade, and information on the conservation status and distribution are presented.